Long-lasting BDNF signaling alterations in the amygdala of adolescent female rats exposed to the activity-based anorexia model - Mottarlini, Francesca; Rizzi, Beatrice; Targa, Giorgia; Fumagalli, Fabio; Caffino, Lucia (Frontiers in Behavioral Neuroscience, 2022)
Introduction: Anorexia nervosa (AN) is a severe psychiatric disorder characterized by a pathological fear of gaining weight, excessive physical exercise, and emotional instability. Since the amygdala is a key region for emotion processing and BDNF has been shown to play a critical role in this process, we hypothesized that alteration in the amygdalar BDNF system might underline vulnerability traits typical of AN patients. Methods: To this end, adolescent female rats have been exposed to the Activity-Based Anorexia (ABA) protocol, characterized by the combination of caloric restriction and intense physical exercise. Results: The induction of the anorexic phenotype caused hyperactivity and body weight loss in ABA animals. These changes were paralleled by amygdalar hyperactivation, as measured by the up-regulation of cfos mRNA levels. In the acute phase of the pathology, we observed reduced Bdnf exon IX, exon IV, and exon VI gene expression, while mBDNF protein levels were enhanced, an increase that was, instead, uncoupled from its downstream signaling as the phosphorylation of TrkB, Akt, and S6 in ABA rats were reduced. Despite the body weight recovery observed 7 days later, the BDNF-mediated signaling was still downregulated at this time point. Discussion: Our findings indicate that the BDNF system is downregulated in the amygdala of adolescent female rats under these experimental conditions, which mimic the anorexic phenotype in humans, pointing to such dysregulation as a potential contributor to the altered emotional processing observed in AN patients. In addition, since the modulation of BDNF levels is observed in other psychiatric conditions, the persistent AN-induced changes of the BDNF system in the amygdala might contribute to explaining the onset of comorbid psychiatric disorders that persist in patients even beyond recovery from AN.